How do stakeholders perceive the sustainability and resilience of EU farming systems? - Pytrik Reidsma; Miranda Meuwissen; Francesco Accatino; Franziska Appel; Isabel Bardaji; Isabeau Coopmans; Camelia Gavrilescu; Florian Heinrich; Vitaliy Krupin; Gordana Manevska-Tasevska; Mariya Peneva; Jens Rommel; et al. (EuroChoices, 2020)
An increasing variety of stresses and shocks provides challenges and opportunities for EU farming systems. This article presents findings of a participatory assessment on the sustainability and resilience of eleven EU farming systems, to inform the design of adequate and relevant strategies and policies. According to stakeholders that participated in workshops, the main functions of farming systems are related to food production, economic viability and maintenance of natural resources. Performance of farming systems assessed with regard to these and five other functions was perceived to be moderate. Past strategies were often geared towards making the system more profitable, and to a lesser extent towards coupling production with local and natural resources, social self-organisation, enhancing functional diversity, and facilitating infrastructure for innovation. Overall, the resilience of the studied farming systems was perceived as low to moderate, with robustness and adaptability often dominant over transformability. To allow for transformability, being reasonably profitable and having access to infrastructure for innovation were viewed as essential. To improve sustainability and resilience of EU farming systems, responses to short-term processes should better consider long-term processes. Technological innovation is required, but it should be accompanied with structural, social, agro-ecological and institutional changes.
Keywords: 330